Cost‐effectiveness of onabotulinumtoxinA for the treatment of wrist and hand disability due to upper‐limb post‐stroke spasticity in Scotland. Issue 5 (24th December 2012) - Doan, Q. V.; Gillard, P.; Brashear, A.; Halperin, M.; Hayward, E.; Varon, S.; Lu, Z. J.
<x xml:space="preserve">Abstract</x> Background and purpose The objective was to evaluate the cost‐effectiveness of treating upper‐limb post‐stroke spasticity (ULPSS) with usual care (UC) plus onabotulinumtoxinA versus UC alone in Scotland. Methods We developed a model to simulate costs and quality‐adjusted life years (QALYs) gained from treating ULPSS. Efficacy data and health utilities were taken from clinical trials. Unit costs were taken from published Scottish sources. We compared UC plus onabotulinumtoxinA and UC alone in three scenarios: (i) a scenario from the National Health Service perspective, which included differences in onabotulinumtoxinA use, specialist visits and day‐hospital visits; (ii) a scenario that only included differences in onabotulinumtoxinA use and specialist visits; and (iii) a scenario from a societal perspective that included differences in onabotulinumtoxinA use, specialist visits and caregiver burden. Results In the first scenario, the model predicted that UC plus onabotulinumtoxinA produced 0.107 QALYs at an additional cost of £1099 compared with UC alone over 5 years, resulting in an incremental cost‐effectiveness ratio (ICER) of £10 271/QALY. In the second scenario, the ICER increased to £27 134/QALY. In the third scenario (societal perspective), UC plus onabotulinumtoxinA produced lower total cost and higher QALYs, and therefore was superior to UC alone. Conclusions Based on a model, UC plus onabotulinumtoxinA improved disability, which translated into greater QALYs but also increased direct medical costs compared with UC alone; however, the resulting ICER can be considered cost‐effective. Moreover, UC plus onabotulinumtoxinA can be cost‐saving if reduction in caregiver burden was included. OnabotulinumtoxinA offers value for money in the management of ULPSS in Scotland.